1993
DOI: 10.1016/0014-5793(93)81700-a
|View full text |Cite|
|
Sign up to set email alerts
|

GTP‐binding protein‐activator sequences in the insulin receptor

Abstract: Some functions of the insulin receptor (insR) are assumed to be mediated by pertussis toxin‐sensitive Gi/Go. proteins. Here we have located G‐protein‐activator domains in the cytoplasmic region of the human insR. We searched the sequence of insR and found three candidate regions at residues 1039‐1061, 1147‐1168 and 1325‐1345, referred to as ISRP 1, ISRP2 and ISRP3, respectively. Among them, the Gi/Go‐activating function was observed only in peptide ISRP3. ISRP1 specifically activated G3, whereas ISRP2 had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Similar co-precipitation of the insulin receptor with G s , G␣ i2 , and G␤␥ has been observed, along with insulin-dependent GTP-loading of G␣ i2 in adipocyte membranes (25). Three purified peptides derived from sequences in the insulin receptor ␤ subunit have been shown to accelerate GTP exchange on purified heterotrimeric G proteins in vitro (33), although this result has not been reproduced with the intact receptor. Two of these peptides contain sites of tyrosine autophosphorylation, and the one corresponding to residues 1325-1345 of the receptor activates G i/o only when tyrosine is phosphorylated.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar co-precipitation of the insulin receptor with G s , G␣ i2 , and G␤␥ has been observed, along with insulin-dependent GTP-loading of G␣ i2 in adipocyte membranes (25). Three purified peptides derived from sequences in the insulin receptor ␤ subunit have been shown to accelerate GTP exchange on purified heterotrimeric G proteins in vitro (33), although this result has not been reproduced with the intact receptor. Two of these peptides contain sites of tyrosine autophosphorylation, and the one corresponding to residues 1325-1345 of the receptor activates G i/o only when tyrosine is phosphorylated.…”
Section: Discussionmentioning
confidence: 71%
“…The first proposal is that the receptors possess the ability to directly catalyze heterotrimeric G protein guanine nucleotide exchange (32). Consistent with this, several groups have reported that heterotrimeric G protein subunits co-precipitate with the IGF-1 and insulin receptors (22,23,25) or have demonstrated that small peptides derived from the insulin and IGF-2 receptors promote a mastoparan-like acceleration of GTP exchange on purified heterotrimeric G proteins in vitro (31,(33)(34)(35). The second model advanced to explain heterotrimeric G protein-dependent signaling by non-GPCRs is that the receptors generate some signal that activates an endogenous GPCR, which in turn catalyzes G protein activation.…”
mentioning
confidence: 94%
“…One possibility might involve the phosphorylation of G i by the PDGFR kinase, although there is no evidence to support this. Others have shown that peptides derived from another growth-factor receptor, insulin-receptor β subunit, activate G i in lipid vesicles [19], suggesting direct protein-protein interaction. Direct interaction between growth-factor receptors and G-proteins has been demonstrated [20][21][22].…”
Section: Role Of C-srcmentioning
confidence: 99%
“…The insulin-like growth factor II receptor has a single transmembrane domain and couples directly to G i2 in a manner similar to that of conventional G-protein-coupled receptors (7). Studies have been reported suggesting that the insulin receptor binds G i ␣ 2 (8,9).…”
mentioning
confidence: 99%